DAMPAK KEBIJAKAN PEMBANGUNAN PERUMAHAN (STUDI DI DESA SEA KECAMATAN PINELENG KABUPATEN MINAHASA) - KALAMPUNG, GERRY ALFERO; LALOMA, ALDEN; KOLONDAM, HELLY (Sam Ratulangi University, 2019)
The purpose of this study was to determine the impact of public housing development policies inthe Sea Village of Minahasa Regency. This study uses a descriptive-cumulative approach. Researchinformants were the village head, housing residents, and community leaders / residents of the Sea Village.The data analysis technique used is an interactive model analysis of Miles and Hubernann. ResearchResults Show: (1) Housing development policies in Sea Village have a positive impact on public matters andon the target group's policy community, which is to help people who do not yet have a home to get housingloans with affordable installments, and in locations that are accessible comfortable and safe. Housingdevelopment does not have the expected impact of disturbing security and comfort in society. Theunexpected impact is mainly the reduction in agricultural land and community forestry. (2) Housingdevelopment policies have a positive impact on economic and social conditions in Sea Village, namelyincreasing people's income and increasing the progress of social life such as education, social andcommunity social activities, and development participation. (3) Housing development policies have apositive impact on current conditions in Sea Village, namely increasing the progress and development ofthe village and community now and in the future. (4) Housing development policies in Sea Village do nothave an impact on the direct and indirect costs that must be borne by the community as a result of thehousing construction.Keywords: Impact of Policy, Housing Development